Mapping Maternal Determinants of Severe Stunting: A GIS-Informed Approach to Health Equity and Spatial Literacy - Erina Sukma Zerlinda; Djoko Soelistijo (CV Bumi Spasial, 2025)
Stunting is a chronic growth failure linked to inadequate nutrition and repeated health stressors during the first 1,000 days of life, commonly manifested as height-for-age below expected standards. Beyond a biomedical condition, stunting is also a place-based socio-spatial phenomenon shaped by unequal access to services, information, and resources. This study investigates the internal distribution of maternal factors among children already diagnosed with stunting in Tanggunggunung District, Tulungagung Regency, an area with the highest local stunting prevalence and geographically constrained accessibility. Maternal factors examined include maternal age, maternal height, maternal knowledge level, daily nutritional intake during pregnancy, maternal health condition during pregnancy, and exclusive breastfeeding. Guided by Mosley and Chen’s (1984) child survival framework, the study interprets stunting as an indicator of morbidity and a precursor of survival risk, while emphasizing how distal geographic constraints may operate through proximal maternal mechanisms. Using a descriptive correlational design with a quantitative approach, the study surveyed 52 mothers selected via systematic random sampling from a population of 105 mothers of stunted children. Data were collected through structured interviews and analyzed using univariate statistics and chi-square tests. Results show significant associations between maternal factors and stunting severity, with significance values as follows: maternal age (p = 0.001), maternal height (p = 0.001), maternal health condition (p = 0.001), exclusive breastfeeding (p = 0.001), maternal knowledge (p = 0.007), and daily nutritional intake (p = 0.011). These findings underscore the need for interventions that address maternal risks within geographically specific contexts and support Geography Education by providing an authentic case for spatial thinking and GIS-informed inquiry on health equity and the SDGs.